Extraction and Characterization of Silica from Reeds Biomass (Imperata cylindrical) in Various Annealing Temperature - Wardani, Dyah Ayu Pramoda; Kurniawati, Neny; Hariyanto, Budi; Har, Nazopatul Patonah; Darmawan, Noviyan; Umam, Rofiqul; Irzaman, Irzaman (Photonics Letters of Poland, 2023)
Reeds biomass has been successfully extracted. It calcinated with annealing temperatures at 800 °C (A800), 850 °C (A850), and 900 °C (A900). The x-ray pattern showed that it has a cristoballite (SiO2) crystal structure. The band gap energy values are 3.8 eV, 3.7 eV and 4.7 eV, respectively. FTIR spectra show the groups are silanol, siloxane, and monohydride. Quantitatively, it provide results to determine the optical properties and dielectric functions which indicate shift to longer wavelengths with an increase in annealing temperature. The morphology gives different image where the particles are formed flakes (A800), aggregates (A850) and porous aggregates (A900). Full Text: PDF References A. F. Ramdja, R. A. Silalahi, N. Sihombing, "Pengaruh waktu, temperatur dan dosis H2SO4 pada hidrolisa asam terhadap kadar etanol berbahan baku alang-alang," J. Tek. Kim., 17, (2010). CrossRef Z. S. Osvaldo, P. Putra, M. Faizal, "Pengaruh konsentrasi asam dan waktu pada proses hidrolisis dan fermentasi pembuatan bioetanol dari alang-alang," J. Tek. Kim., 18, (2012). CrossRef I. S. Naji, N. A. Khalifa, and H. M. Khalaf, "Influence of annealing temperature on the physical properties of thin Cu2SiO4 films prepared by pulsed laser deposition," Dig. J. Nanomater. Biostructures, 12, 899 (2017). DirectLink M. Sahri, A. R. Tualeka, N. Widajati, "Quantitative risk assesment of crystalline silica exposure in ceramics industry," Indian J. Public Heal. Res. & Dev., 10, 601 (2019). CrossRef A. Berendjchi, R. Khajavi, M. E. Yazdanshenas, "Application of nanosols in textile industry," Int. J. Green Nanotechnol., 1, 1943089213506814 (2013). CrossRef P. Y. Steinberg, "Structural and mechanical properties of silica mesoporous films synthesized using deep X-rays: implications in the construction of devices," Front. Mater., 8, 27 (2021). CrossRef A. F. Lourenço, J. A. F. Gamelas, J. Sequeira, P. J. Ferreira, J. L. Velho, "Improving paper mechanical properties using silica-modified ground calcium carbonate as filler," BioResources, 10, 8312 (2015). CrossRef S. Begum, M. Allaudin, M. A. Qaiser, and F. KHAN, "Beneficiation of silica sand for the manufacturing of optical glass". J.Chem. Soc. Pakistan, 21, 83 (1999). DirectLink N. H. N. A. Hadi, A. Anuar, R. K. Shuib, "Effect of Different Salinization Methods of Silica Filler on Rubber Reinforcement," J. Eng., 15, 71 (2019). CrossRef K. Kayed and D. B. Kurd, "The effect of annealing temperature on the structural and optical properties of Si/SiO2 composites synthesized by thermal oxidation of silicon wafers," Silicon, 14, 5157 (2021). CrossRef F. Ravaux, N. S. Rajput, J. Abed, L. George, M. Tiner, M. Jouiad, "Effect of rapid thermal annealing on crystallization and stress relaxation of SiGe nanoparticles deposited by ICP PECVD," RSC Adv.,7, 32087 (2017). CrossRef H. Liu et al., "Design and synthesis of carbon-coated α-Fe2O3-Fe3O4 heterostructured as anode materials for lithium ion batteries," Appl. Surf. Sci., 495, 143590 (2019). CrossRef M. Ghasemifard, E. Fathi, M. Ghamari, "The effect of Fe3+-doped on structure and optical properties of mesoporous Al2O3/SiO2 composite," Mater. Sci. Semicond. Process., 42, 349 (2016). CrossRef X. Lu et al., "Effect of high-intensity ultrasound irradiation on the stability and structural features of coconut-grain milk composite systems utilizing maize kernels and starch with different amylose contents," Ultrason. Sonochem., 55, 135 (2019). CrossRef E. W. Juni, A. Arnelli, S. Sriatun, "Pemanfaatan Surfaktan Kationik Hasil Sublasi sebagai Molekul Pengarah pada Pembuatan Material Berpori dari Sekam Padi," J. Kim. Sains dan Apl., 15, 24 (2012). CrossRef F. Adam, K. Kandasamy, S. Balakrishnan, "Iron incorporated heterogeneous catalyst from rice husk ash," J. Colloid Interface Sci., 304, 137 (2006). CrossRef K. C. Wong, "Review of spectrometric identification of organic compounds." J. Chem. Educ., 92, 1602 (2015). CrossRef L. H. Abuhassan, "Enhancement of the production yield of fluorescent silicon nanostructures using silicon-based salts," Sains Malaysiana, 39, 837 (2010). DirectLink U. Kalapathy, A. Proctor, J. Shultz, "Silica xerogels from rice hull ash: structure, density and mechanical strength as affected by gelation pH and silica concentration", J. Chem. Technol. & Biotechnol., 75, 464 (2000) CrossRef